Endobronchial actinomycosis in a child. Issue 10 (15th July 2021) - Goussard, Pierre; Rabie, Helena; Marshall, Michelle; Mfingwana, Lunga; Morrison, Julie; Ismal, Zane; Retief, Francois; Nel, Pieter; Da Costa, Dawood; Andronikou, Savvas; Schubert, Pawel
Abstract: Actinomycosis is a rare, indolent and invasive infection caused by Actinomyces species. Pulmonary actinomycosis is very rarely seen in the paediatric population. The classic radiological presentation of thoracic involvement of actinomycosis includes lower lobe consolidation, empyema and periostitis of the ribs. We report a case of endobronchial actinomycosis in a child diagnosed on endobronchial biopsy and bronchoalveolar lavage (BAL). Bronchoscopy can be dangerous when performed on these cases, as there is a risk of severe bleeding and large airway obstruction, as was the case with this patient.